2017
DOI: 10.1515/aiht-2017-68-2843
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fertiliser treatments on the severity of Fusarium head blight and mycotoxin biosynthesis in winter rye

Abstract: The fungi of the genus Fusarium cause Fusarium head blight (FHB), a devastating disease that reduces grain yield and quality. They also produce mycotoxins which may pose a serious threat to human and animal health. This study investigated the effects of NPK fertilisation, foliar application of Cu, Zn, and Mn, applied separately and in combination, and of the Nano-Gro ® organic growth stimulator on the occurrence of FHB in cultivar Dańkowskie Diament rye based on the mycological analysis of kernels and on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Mesterhazy (1997) [19] reported that DON levels in wheat depends on both variety resistance and isolate. In wheat, barley, and rye, the severity of symptoms on spike is often correlated with the mycotoxin accumulation in the grains [20,21,22,23,24]. However, for DON content, it was concluded that is not always highly correlated with FHB severity because those traits could be regulated by independent loci or genes [25].…”
Section: Introductionmentioning
confidence: 99%
“…Mesterhazy (1997) [19] reported that DON levels in wheat depends on both variety resistance and isolate. In wheat, barley, and rye, the severity of symptoms on spike is often correlated with the mycotoxin accumulation in the grains [20,21,22,23,24]. However, for DON content, it was concluded that is not always highly correlated with FHB severity because those traits could be regulated by independent loci or genes [25].…”
Section: Introductionmentioning
confidence: 99%
“…More than 400 different types of mycotoxins have been identified with different levels of toxicity. Among all mycotoxins, aflatoxins (AFs), Ochratoxin A (OTA), patulin (PAT), Zearalenone (ZEN), and Trichothecenes (TCT) have received particular attention due to their severe health outcomes on both humans and animals that can range from acute to severe and chronic intoxications in both humans and animals (Milićević et al 2010;Cwalina-Ambroziak et al 2017;Vargas et al 2001;El Khoury and Atoui 2010;El Khoury et al 2011;Battilani et al 2016;Nahle et al 2020). Exposure to mycotoxins can occur directly through the ingestion of contaminated food or indirectly through bi-products of animals consuming contaminated feed (Bullerman 1979).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously stated that 20-40% of crops have been said to be lost each year due to pests and diseases, furthermore 25% of grain crops are contaminated with mycotoxins, mainly with deoxynivalenol (DON) as one of the five most commonly occurring (Worrall et al, 2018;Bryden, 2011;Rodrigues and Naehrer, 2012). Plant disease is a major problem for production, and the decrease in crop yield (Ramezani et al, 2019;Cwalina-Ambroziak et al, 2017). Wheat is one of the most prone crops to mycotoxin contamination in temperate regions, such as DON or T-2 toxins.…”
Section: Introductionmentioning
confidence: 99%